2013
DOI: 10.1093/ejcts/ezt553
|View full text |Cite
|
Sign up to set email alerts
|

Herniation of an abdominal antireflux fundoplication into the chest: what does it mean?

Abstract: OBJECTIVES:The specific contribution of the herniation of an abdominal antireflux fundoplication into the chest to symptomatic and therefore surgical failure remains unclear. METHODS:The study was conducted in 189 consecutive fundoplication patients, categorized as patients reoperated on for chest herniation of either an abdominal 360°(Group 1; n = 95) or a partial (Group 2; n = 10) fundoplication, and patients having undergone an intrathoracic 360°fundoplication for short oesophagus (Group 3; n = 84; referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Lastly, axial tension also needs to be recognized in the form of a shortened esophagus and should be addressed in the primary and revision operation using the techniques of Collis gastroplasty or the Nissen-Hill hybrid approach, as was used in some patients in this series [26,27]. This notion has also been expanded in a recent study analyzing fundoplication herniations into the chest, which identified that patients with a short esophagus may not be good candidates for ARS because a slipped or perigastric wrap was found not to function properly in the chest [28]. One of the key issues raised in performing revision ARS is the higher complication rate and associated morbidity.…”
Section: Commentmentioning
confidence: 97%
“…Lastly, axial tension also needs to be recognized in the form of a shortened esophagus and should be addressed in the primary and revision operation using the techniques of Collis gastroplasty or the Nissen-Hill hybrid approach, as was used in some patients in this series [26,27]. This notion has also been expanded in a recent study analyzing fundoplication herniations into the chest, which identified that patients with a short esophagus may not be good candidates for ARS because a slipped or perigastric wrap was found not to function properly in the chest [28]. One of the key issues raised in performing revision ARS is the higher complication rate and associated morbidity.…”
Section: Commentmentioning
confidence: 97%